2000
DOI: 10.1536/jhj.41.451
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Appendage Function in Patients with Chronic Nonvalvular Atrial Fibrillation.

Abstract: SUMMARYTo assess right atrial appendage (RAA) flow and its possible relationship to left atrial appendage (LAA) flow in chronic nonvalvular atrial fibrillation (AF), transesophageal echocardiography (TEE) was performed in 26 patients with chronic nonvalvular AF (group I). For the purpose of comparison, an additional group of 27 patients with chronic valvular AF due to mitral stenosis (group II) was analyzed. The clinically estimated duration of AF in group I was significantly longer than that of group II (8.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Relationship between the dimensions and function of the right atrium and occurrence of AF is properly documented [35,36]. Enlargement and remodeling of both atria predispose to development of AF.…”
Section: The Right Heart In Patients With Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship between the dimensions and function of the right atrium and occurrence of AF is properly documented [35,36]. Enlargement and remodeling of both atria predispose to development of AF.…”
Section: The Right Heart In Patients With Atrial Fibrillationmentioning
confidence: 99%
“…Studies using stress echocardiography showed the prognostic values of the right atrium area to maintain sinus rhythm after AF ablation [35]. However, on the basis of existing evidence, area of the right atrium can be used to assess prognosis only in patients with non-valvular AF [36].…”
Section: The Right Heart In Patients With Atrial Fibrillationmentioning
confidence: 99%
“…Our study was not designed to address a possible mechanistic explanation of such changes; central hemodynamic derangements in patients with heart failure represent a complex interplay of several factors, such as impaired ventricular pump function, atrial contractility and the functional integrity of the mitral apparatus, among others. [26][27][28] Moreover, patients at high risk of thrombus formation because of cardiac hemodynamic derangements (ie, patients with severely impaired LVEF or atrial fibrillation) have to be anticoagulated [29][30][31][32] and were thus excluded from our study (anticoagulation therapy was an exclusion criterion in order to avoid obvious confounding interactions between anticoagulation therapy and hemostatic derangements). In our study, transthoracic echocardiographic imaging did not detect a thrombus in any of the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is no wonder that thrombi can form also in the RA, and especially in its appendage (Fig. 6) [55,56]. There are serious reasons to assume that dysfunction of RAA in AF may cause thrombi formation in the right heart.…”
Section: Right Atrial Appendagementioning
confidence: 99%
“…In various studies, the incidence of SEC and thrombi in the RA and its appendage in patients with AF ranged between 1-7.5% and 10-57% [56][57][58][59]. Although systemic thromboembolism risk is mostly studied, pulmonary embolism is also possible in patients with AF.…”
Section: Right Atrial Appendagementioning
confidence: 99%